(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study examined business process management and business communication as correlates of effective performance in small and medium scale enterprises (SMEs) in Abia State, Nigeria. Two research questions guided the study while two research hypotheses were tested. The study adopted correlational design. The population of the study comprised 1,809 entrepreneurs of small and medium-scale enterprises registered with Abia State Ministry of Trade and Investment. Simple random sampling technique was used to sample 226 SME managers for the study. Structured questionnaire was used for data collection. Three experts were used to validate the instrument for data collection. Reliability of the instrument was established using Cronbach’s alpha and it yielded alpha values of 0.79, 0.81, and 0.77 for the three clusters, respectively. Data analysis was done using Pearson correlation coefficient and multiple regression analysis. Findings from the study revealed that there was a significant positive correlation between business communication and effective SME performance. No significant positive correlation was found between business process management and effective SME performance. Based on the findings, it was recommended that owners and managers of SMEs should as matter of necessity install a functional communication system for effective communication among all stakeholders of the business enterprise in order to achieve effective performance.